Preparation method and application of dynamic crosslinked polyethylene for electrical damage repair
By preparing dynamic crosslinked polyethylene materials in polyethylene cable insulation materials, the problems of self-repair and recyclability of electrical damage are solved, and efficient repair and sustainable utilization of materials are achieved, and are suitable for the field of power cables.
Patent Information
- Application Number
- CN202411811573.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The prior art is difficult to achieve self-repair and recyclable characteristics of electrical damage in cable insulation materials, and is costly and difficult to operate, which limits large-scale applications in the power cable industry.
By rotary evaporating the polyethylene particles with peroxide, a crosslinkable insulating material is obtained, and graft monomer and reaction monomer are added in a melted state, and the dynamic crosslinked polyethylene material is prepared. The material can be self-healed after electrical damage and has recyclable properties.
It realizes self-repair, recycling and reuse of polyethylene materials, maintains high mechanical properties and insulation properties, is simple to operate, easy to obtain raw materials, and has broad application prospects.
Smart Images

Figure CN119798545A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polyethylene cable insulation materials, and in particular to a preparation method and application of dynamically cross-linked polyethylene for electrical damage repair. Background Art
[0002] Cross-linked polyethylene (XLPE) is a material with a three-dimensional mesh structure. It is widely used in the field of power cables due to its excellent mechanical properties, heat resistance and insulation properties. However, in high-voltage environments, cables are prone to electrical damage, such as electrical breakdown, corona damage and electrical tree damage. Electrical breakdown causes local breakdown of the insulating material, the corona phenomenon accelerates the degradation of the insulation layer, and electrical tree damage forms dendritic cracks that gradually extend to cable breakdown. These phenomena seriously affect the stability, reliability and long-term usability of cable insulation materials.
[0003] The invention patent with publication number CN 112358631 B discloses a method for preparing a dynamic covalently cross-linked polyethylene material, which achieves the transformation and reorganization of the polymer network through a reversible exchange reaction between different borate groups. However, the dynamic covalently cross-linked polyethylene material obtained by this technology does not involve the exploration of self-repair performance after electrical damage, and has disadvantages such as high cost and difficult operation, which is not conducive to large-scale application in the power cable industry. In addition, XLPE cables cannot be recycled after retirement, and are usually incinerated or landfilled, which will cause serious environmental pollution and waste of resources.
[0004] Therefore, how to give cross-linked polyethylene cable insulation materials self-repair and recyclability properties for electrical damage has become a difficult problem in the prior art. Summary of the invention
[0005] The purpose of the present invention is to solve the deficiencies of the prior art and provide a method for preparing a dynamically cross-linked polyethylene for electrical damage repair and its application. The method can achieve self-repair and recyclability of polyethylene while maintaining a high level of mechanical properties and insulation properties, and has the advantages of simple operation and easy availability of raw materials. The present invention has broad prospects in producing high-performance polyethylene materials, achieving self-repair, recycling and reuse of polyethylene materials, etc.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing dynamically cross-linked polyethylene for electrical damage repair, comprising the following steps:
[0008] (1) Rotary evaporation of polyethylene particles and peroxide to obtain semi-finished particles of mixed peroxide, and then post-absorption to obtain cross-linkable insulating material;
[0009] (2) adding a grafting monomer and a reactive monomer to the cross-linkable insulating material obtained in step (1), reacting them in a molten state to obtain a mixed block;
[0010] (3) The mixed block obtained in step (2) is subjected to hot pressing to obtain a dynamically cross-linked polyethylene material.
[0011] Preferably, in step (1), the peroxide is at least one selected from dicumyl peroxide, di-tert-butyl peroxycumene, methyl ethyl ketone peroxide, hexane peroxide, tert-butyl hydroperoxide and di-tert-butyl peroxide.
[0012] Preferably, in the step (1), in the mixture of polyethylene particles and peroxide, the mass content of peroxide is 0.2% to 2.0%.
[0013] Preferably, in step (1), the post-absorption temperature is 60-80° C., and the post-absorption time is 0-48 h.
[0014] Preferably, in step (2), the grafting monomer is selected from at least one of maleic anhydride, methyl acrylate and methyl methacrylate; and the reactive monomer is selected from at least one of butanediol, 2-hydroxyethyl disulfide, hydroquinone and terephthalic acid alcohol.
[0015] Preferably, in step (2), the mass ratio of the grafting monomer to the cross-linkable insulating material is (1-10):100.
[0016] Preferably, in step (2), the molar ratio of the reactive monomer to the grafting monomer is (0.5-3):2.
[0017] Preferably, in step (2), the melt blending temperature is 100-180° C., and the melt blending time is 5-30 min.
[0018] Preferably, in step (3), the hot pressing temperature is 120-200° C., and the hot pressing time is 6-180 min.
[0019] The invention also provides a dynamically cross-linked polyethylene material prepared by the preparation method.
[0020] The present invention also provides application of the dynamic cross-linked polyethylene material as an insulating material in the field of power cables.
[0021] The present invention has the following beneficial effects:
[0022] The present invention provides a method for preparing a dynamically cross-linked polyethylene for electrical damage repair, including adding a reactive monomer during the reaction process, which can realize the self-repair property of the material after electrical damage, and by controlling the ratio of the grafted monomer and the reactive monomer, it can also maintain excellent mechanical properties and electrical insulation properties. The results of the embodiment show that the dynamically cross-linked polyethylene material prepared by the present invention has a good repair effect under the conditions of 120°C and 12h. At the same time, the breakdown strength of the dynamically cross-linked polyethylene material prepared by the present invention can reach 325.9kV / mm, its tensile strength can reach 17.3MPa, and its elongation at break can reach 1300%, with excellent mechanical properties and electrical insulation properties. The tensile strength of the sample repaired after mechanical damage is about 94% of the initial state, the elongation at break is about 100% of the initial state, and the breakdown strength of the sample repaired after corona damage is about 100% of the initial state, indicating that the dynamically cross-linked polyethylene material has good self-repair properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 Fourier infrared spectra of polyethylene prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 2;
[0025] Figure 2 The breakdown strength of the dynamically cross-linked polyethylene prepared in Example 2 of the present invention and Comparative Example 1;
[0026] Figure 3 The mechanical damage and mechanical properties after repair of the dynamically cross-linked polyethylene prepared in Example 2 of the present invention;
[0027] Figure 4 A schematic diagram of electrical tree damage and repair of the dynamically cross-linked polyethylene prepared in Example 2 of the present invention;
[0028] Figure 5 The breakdown strength of the dynamically cross-linked polyethylene prepared in Example 2 of the present invention before and after corona damage and after corona repair. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0030] The present invention provides a method for preparing dynamically cross-linked polyethylene for electrical damage repair, comprising the following steps:
[0031] (1) Rotary evaporation of polyethylene particles and peroxide to obtain semi-finished particles of mixed peroxide, and then post-absorption to obtain cross-linkable insulating material;
[0032] (2) adding a grafting monomer and a reactive monomer to the cross-linkable insulating material obtained in step (1), reacting them in a molten state to obtain a mixed block;
[0033] (3) The mixed block obtained in step (2) is subjected to hot pressing to obtain a dynamically cross-linked polyethylene material.
[0034] Unless otherwise specified, the present invention has no particular limitation on the sources of the components, and commercially available products known to those skilled in the art may be used.
[0035] In the present invention, the peroxide is preferably selected from at least one of dicumyl peroxide, di-tert-butyl peroxy isopropyl benzene, butanone peroxide, hexane peroxide, tert-butyl hydroperoxide and di-tert-butyl peroxide, more preferably dicumyl peroxide, tert-butyl hydroperoxide and di-tert-butyl peroxide, and most preferably dicumyl peroxide. As an initiator, the peroxide decomposes and generates free radicals under the action of heat, captures hydrogen atoms on the macromolecular chain, and generates macromolecular chain free radicals. At the same time, since the cross-linked polyethylene itself has a three-dimensional network structure, the peroxide also plays the role of a crosslinking agent therein.
[0036] In the present invention, in the mixture of polyethylene particles and peroxide, the mass content of peroxide is preferably 0.2% to 2.0%. The amount of peroxide added needs to be controlled within a certain proportion, otherwise it will not only affect the performance of the material, but also cause waste.
[0037] In the present invention, the post-absorption temperature is preferably 60-80°C, more preferably 70°C; the post-absorption time is preferably 0-48h, more preferably 3-36h, and most preferably 6-24h. The present invention limits the post-absorption temperature and time within the above ranges, which can make the reaction proceed more fully.
[0038] In the present invention, the grafting monomer is preferably selected from at least one of maleic anhydride, methyl acrylate and methyl methacrylate, and more preferably maleic anhydride. Taking maleic anhydride as a grafting monomer as an example, under the action of peroxide, the maleic anhydride monomer is activated and can capture a hydrogen atom on the polyethylene macromolecular chain to form polyethylene free radicals and maleic anhydride free radicals respectively, and the two are coupled and terminated to generate polyethylene grafted maleic anhydride.
[0039] In the present invention, the reactive monomer is preferably selected from one of butanediol, 2-hydroxyethyl disulfide, hydroquinone and terephthalimethanol. The hydroxyl groups at both ends of the reactive monomer can react with maleic anhydride on the polyethylene chain respectively, acting as a cross-linking agent to form a cross-linked network structure. More preferably, it is 2-hydroxyethyl disulfide. The 2-hydroxyethyl disulfide not only has a group that can react with maleic anhydride, but also has a dynamically reversible disulfide bond, which can give the material dual dynamic characteristics and further improve the self-healing efficiency of the material.
[0040] In the present invention, the mass ratio of the grafting monomer to the cross-linkable insulating material is preferably (1-10):100, and more preferably (2-8):100.
[0041] In the present invention, the molar ratio of the reactive monomer to the grafted monomer is preferably (0.5-3):2, more preferably (1-2):2. If the reactive monomer is added in excessive amounts, the mechanical properties (tensile strength and elongation at break) and insulation properties (breakdown strength) of the material will decrease; if the grafted monomer is added in excessive amounts, the mechanical properties (tensile strength and elongation at break) and insulation properties of the material will also decrease. Otherwise, the improvement of polyethylene performance is limited.
[0042] In the present invention, the temperature of the melt blending is preferably 100-180° C., more preferably 110-150° C.; the time of the melt blending is preferably 5-30 min, more preferably 6-20 min.
[0043] In the present invention, the hot pressing temperature is preferably 120-200° C., more preferably 120-180° C.; the hot pressing time is preferably 6-180 min, more preferably 6-120 min.
[0044] In the present invention, the rotary evaporation is preferably carried out in an evaporating flask of a rotary evaporator.
[0045] In the present invention, the post-absorption is preferably carried out in a blast drying oven.
[0046] In the present invention, the melt blending is preferably carried out in a torque rheometer.
[0047] In the present invention, the heat pressing treatment is preferably performed in a heat press.
[0048] The present invention provides a dynamically cross-linked polyethylene material prepared by the preparation method. In the present invention, the thickness of the material is preferably 0.03-2 mm.
[0049] The dynamically cross-linked polyethylene material prepared by the invention has the self-repairing properties of electrical breakdown, corona and electrical tree damage.
[0050] The present invention also provides the application of the dynamic cross-linked polyethylene material in the field of power cable insulation materials. The application of the dynamic cross-linked polyethylene material in the field of power cable insulation materials is not particularly limited, and the technical solutions for the application of cross-linked polyethylene in the field of power cable insulation materials well known to those skilled in the art can be adopted.
[0051] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Example 1
[0053] A certain amount of polyethylene particles were placed in a rotary evaporator evaporation bottle, dicumyl peroxide was added according to the mass percentage, and the mixture was rotary evaporated at 70°C for 20 min. The semi-finished particles mixed with dicumyl peroxide were kept in a 70°C oven and absorbed for 15 hours to obtain a cross-linked insulating material, and 100 parts by weight of the cross-linked insulating material contained 1.8 parts by weight of peroxide; then 100 parts by weight of the cross-linked insulating material, 4.16 parts by weight of maleic anhydride and 3.27 parts by weight of 2-hydroxyethyl disulfide were melt blended at 130°C for 5 minutes at a speed of 100 rpm / min. (At this time, the molar ratio of maleic anhydride to 2-hydroxyethyl disulfide was 2:1.4). The mixed block was naturally cooled, and finally pre-pressed at 120°C for 6 minutes and hot-pressed at 150°C for 1 hour in a hot press to obtain a dynamically cross-linked polyethylene material, which was recorded as PE-MA-HEDS1.
[0054] Example 2
[0055] The 2-hydroxyethyl disulfide in Example 1 was replaced with 4.58 parts by weight, and the other parameters were the same as those in Example 1 (the molar ratio of maleic anhydride to 2-hydroxyethyl disulfide was 2:1.4 at this time), to obtain a dynamically cross-linked polyethylene material, which was recorded as PE-MA-HEDS2.
[0056] Example 3
[0057] The 2-hydroxyethyl disulfide in Example 1 was replaced with 5.89 parts by weight, and the other parameters were the same as those in Example 1 (the molar ratio of maleic anhydride to 2-hydroxyethyl disulfide was 2:1.8 at this time), to obtain a dynamically cross-linked polyethylene material, which was recorded as PE-MA-HEDS3.
[0058] Comparative Example 1
[0059] The maleic anhydride and 2-hydroxyethyl disulfide in Example 1 were omitted, and the cross-linkable insulating material was pre-pressed at 120° C. for 6 minutes and hot-pressed at 150° C. for 1 hour in a hot press to obtain a cross-linked polyethylene material, which was recorded as XLPE.
[0060] Comparative Example 2
[0061] The 2-hydroxyethyl disulfide in Example 1 was omitted, and other parameters were the same as those in Example 1, thereby obtaining a polyethylene grafted maleic anhydride material, which was denoted as PE-MA.
[0062] Comparative Example 3
[0063] The maleic anhydride in Example 1 was replaced with 5.26 parts by weight (the molar ratio of maleic anhydride to 2-hydroxyethyl disulfide was 2:1.0), and the other parameters were the same as those in Example 1 to obtain a dynamically cross-linked polyethylene material, which was recorded as PE-MA-HEDS4.
[0064] Compared with Example 1, more 2-hydroxyethyl disulfide was added in Examples 2 and 3, and more maleic anhydride was added in Comparative Example 3. The performance test results of the above Examples and Comparative Examples are shown in Table 1.
[0065] Table 1 Performance comparison of different samples
[0066]
[0067] From the data in Table 1, it can be seen that the molar ratio of maleic anhydride to 2-hydroxyethyl disulfide in Example 1 is 2:1.0. The 2-hydroxyethyl disulfide in Example 2 is more than that in Example 1, indicating that more groups react with maleic anhydride and the reaction is fully carried out, so the test data is better than that in Example 1. The performance of Example 3 is reduced because too much 2-hydroxyethyl disulfide is introduced, and the dynamic reaction generated limits the improvement of mechanical properties.
[0068] Compared with Comparative Example 1, Example 2 has higher elongation at break and breakdown strength, but lower tensile strength, which is due to the higher degree of crosslinking in Comparative Example 1, and thus better tensile strength; compared with Comparative Example 2, Example 2 has lower breakdown strength, which is due to the introduction of 2-hydroxyethyl disulfide to form a crosslinked network in the material, so the breakdown strength of Comparative Example 2 is higher. Compared with Example 1, Comparative Example 3 adds too much maleic anhydride, so that a large amount of by-products are produced during the reaction, which reduces its performance.
[0069] The Fourier transform infrared spectra of the polyethylene materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested. The prepared polyethylene materials were cut into small pieces of 30 mm × 30 mm and tested using a Fourier transform infrared spectrometer with a scanning range of 4000 to 600 cm-1 , the results are as follows Figure 1 As shown. Figure 1 It can be seen that, relative to Comparative Example 1, the introduction of grafted groups in Comparative Example 2 can be observed, and dynamically cross-linked polyethylene is successfully prepared in Examples 1 to 4.
[0070] The breakdown strength of the cross-linked polyethylene prepared in Example 2 and Comparative Example 1 was tested by using a pressure test device (RK2674-A; China MEIRUIKE Company). The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the breakdown strength of the dynamically cross-linked polyethylene prepared in Example 2 is higher than that of the cross-linked polyethylene, and the breakdown strength of the dynamically cross-linked polyethylene can reach 325.9 kV / mm.
[0071] The mechanical properties of the dynamically cross-linked polyethylene prepared in Example 2 before and after repair were tested. The sample was cut into a dumbbell shape and then mechanically damaged. The damaged sample was placed in a blast drying oven at 120°C for repair for 12 hours. The mechanical properties of the sample before and after repair were tested using a MARK-10 tester. The speed of the tensile testing machine was 50 mm / min. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the tensile strength of the repaired sample is about 94% of the initial state, and the elongation at break is about 100% of the initial state, indicating that the dynamically cross-linked polyethylene has good self-healing properties against mechanical damage.
[0072] Schematic diagram of the electrical tree damage and repair of the dynamically cross-linked polyethylene prepared in Test Example 2. The electrical tree test used a steel needle electrode of the XLPE insulating sample, with the needle tip perpendicular to the bottom edge of the sample and a spacing of 2 mm. The industrial frequency AC voltage was applied to the needle electrode through a step-up transformer, and the experimental duration was 20 minutes. The entire process of the initiation and growth of the electrical tree in the insulating sample was recorded by an optical microscope and a video acquisition module. The sample after the electrical tree growth was complete was repaired in a 120°C blast drying oven for 12 hours. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the electrical dendrites of PE-MA-HEDS2 can achieve self-repair through thermal stimulation.
[0073] The breakdown strength of the dynamically cross-linked polyethylene prepared in Example 2 was tested. After the dynamically cross-linked polyethylene was damaged by corona, it was placed in a blast drying oven at 120°C for 12 hours for repair. Then, the breakdown strength before and after repair was tested in a pressure test device (RK2674-A; China MEIRUIKE Company). The results are as follows: Figure 5 As shown. Figure 5It can be seen that the attenuation rate of the breakdown strength of the sample after corona damage is 16%, and the breakdown strength of the sample after repair is about 100% of the initial state.
[0074] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing dynamically cross-linked polyethylene for electrical damage repair, characterized in that: The steps include: (1) Rotary evaporation of polyethylene particles and peroxide to obtain semi-finished particles of mixed peroxide, and then post-absorption to obtain cross-linkable insulating material; (2) adding a grafting monomer and a reactive monomer to the cross-linkable insulating material obtained in step (1), reacting them in a molten state to obtain a mixed block; (3) The mixed block obtained in step (2) is subjected to hot pressing to obtain a dynamically cross-linked polyethylene material.
2. The method for preparing dynamically cross-linked polyethylene for electrical damage repair according to claim 1, characterized in that: In the step (1), the peroxide is selected from at least one of dicumyl peroxide, di-tert-butyl peroxycumene, methyl ethyl ketone peroxide, hexane peroxide, tert-butyl hydroperoxide and di-tert-butyl peroxide.
3. The method for preparing dynamically cross-linked polyethylene for electrical damage repair according to claim 1, characterized in that: In the step (1), in the mixture of polyethylene particles and peroxide, the mass content of peroxide is 0.2% to 2.0%.
4. The method for preparing dynamically cross-linked polyethylene for electrical damage repair according to claim 1, characterized in that: In the step (1), the post-absorption temperature is 60-80° C., and the post-absorption time is 0-48 hours.
5. The method for preparing dynamically cross-linked polyethylene for electrical damage repair according to claim 1, characterized in that: In the step (2), the grafting monomer is selected from at least one of maleic anhydride, methyl acrylate and methyl methacrylate; and the reactive monomer is selected from at least one of butanediol, 2-hydroxyethyl disulfide, hydroquinone and terephthalic acid.
6. The method for preparing dynamically cross-linked polyethylene for electrical damage repair according to claim 1, characterized in that: In the step (2), the mass ratio of the grafting monomer to the cross-linkable insulating material is (1-10):100; the molar ratio of the reactive monomer to the grafting monomer is (0.5-3):
2.
7. The method for preparing dynamically cross-linked polyethylene for electrical damage repair according to claim 1, characterized in that: In the step (2), the temperature of melt blending is 100-180°C, and the time of melt blending is 5-30 minutes.
8. The method for preparing dynamically cross-linked polyethylene for electrical damage repair according to claim 1, characterized in that: In the step (3), the hot pressing temperature is 120-200° C., and the hot pressing time is 6-180 min.
9. The dynamically cross-linked polyethylene material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the dynamically cross-linked polyethylene material according to claim 9 as an insulating material in the field of power cables.
Citation Information
Patent Citations
Dynamically covalently crosslinked materials for enhancing polyethylene properties, their preparation methods and applications
CN112358631B
Ionic crosslinking ultra-high molecular weight polyethylene material with self-repairing function and preparation method thereof
CN110655613A
Recyclable polyethylene cable insulating material
CN111234435A
Dynamic polymer with hybrid cross-linked network
CN111378167A
Self-repairing high-density polyethylene resin and preparation method thereof
CN112920492A
Cited By
Dynamic crosslinked polyethylene as well as preparation method and application thereof
CN121405839A